2013
DOI: 10.7903/cmr.10629
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Anomalies: A Closer Look at the Johannesburg Stock Exchange

Abstract: We examine seasonal anomalies in Johannesburg daily stock returns from January 1973 to September 2012. This paper focuses on three seasonal effects: day-of-the-week, beginning-of-the-month and month-of-the-year. We found no compelling evidence for either a January or December effect in the South African market. Instead, our results support the presence of strong Monday and Tuesday effects, whereby the returns on Monday and Tuesday are significantly lower than the return on the benchmark day of Wednesday. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
(13 reference statements)
2
7
0
Order By: Relevance
“…Our results indicate that the most significant and consistent pattern are on Mondays, where all coefficients are positive, and Fridays, where all coefficients are negative. These results are similar to the findings ofAlagidede (2008),Darrat et al (2013) andNdako (2013), who all used similar statistical techniques to this study and South African data.Moreover, the day-of-the-week effect in both mean and conditional volatility is sensitive to the choice of error distribution. In all the cases, the conditional volatility varies with the days of the week.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our results indicate that the most significant and consistent pattern are on Mondays, where all coefficients are positive, and Fridays, where all coefficients are negative. These results are similar to the findings ofAlagidede (2008),Darrat et al (2013) andNdako (2013), who all used similar statistical techniques to this study and South African data.Moreover, the day-of-the-week effect in both mean and conditional volatility is sensitive to the choice of error distribution. In all the cases, the conditional volatility varies with the days of the week.…”
supporting
confidence: 91%
“…Brusa and Liu (2004) found the traditional weekend effect to be present in the US market, but that it reversed between 1988 and 1998. More recently, Mlambo and Biekpe (2006), Alagidede (2008), Mbululu and Chipeta (2012), Darrat et al (2013) and Plimsoll et al (2013) all confirm the presence of limited and spurious day-of-the week effects on the indices of different African stock markets. However, because results differ across industries, stock markets, and periods, no definitive conclusion about the presence of any such effects can be confirmed.…”
Section: Literaturementioning
confidence: 79%
“…Daily, weekly, and monthly effects can be referred to as seasonalities, where "seasonality is a usual and recurring variation in a time series that occurs occasionally over a span of less than a year" (Prajapati et al, 2013). Therefore, it would be possible for investors to predict stock market developments based on past information and profit from the abnormal returns resulting from these effects (e.g., Darrat et al, 2013;Sharma et al, 2014). This behavior portends market inefficiency, since it should be impossible to generate abnormal returns because of systematic price changes, and these anomalies should not exist in an efficient market (e.g., Safeer and Kevin, 2014;Patel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to explain the calendar effects in the Johannesburg stock Exchange, Darrat, Li and Chung (2013) observed that no compelling evidence for either a January or December effect in South African Market. On the contrary, the study on January effect, Sudarvel and Velmurugan (2015) confirmed the existence of seasonality in stock returns in Bombay Stock Exchange's banking sector and the existence of January effect.…”
Section: Review Of Literaturementioning
confidence: 99%